(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
In an econometric framework, the present study is an examination of the relationship between the consumers’ choice for health insurance and its determinants. The Structural Model assessment has been employed to study the impact of Marketing Variables, Socio-Economic Variables and Cultural values on Consumer Choice in Health Insurance segment. The results have found to be statistically significant which shows that there is impact of Socio-Economic Variables, Marketing Variables, and Cultural values on Consumer Choice.